Electroluminescence of double-doped diamond thin films - 章诗 王小平 王丽军 朱玉传 梅翠玉 刘欣欣 李怀辉 顾应展 (Chinese physics B, 2010)
A new electroluminescence device is fabricated by microwave plasma chemical vapour deposition system and electron beam vapour deposition system. It is comprised of highly doped silicon/diamond/boron/nitrogen-doped diamond/indium tin oxide thin films. Effects of process parameters on morphologies and structures of the thin films are detected and analysed by scanning electron microscopy, Raman spectrometer and x-ray photoelectron spectrometer. A direct-current （DC） power supply is used to drive the electroluminescence device. The blue light emission with a luminance of 1.2 cd·m^-2 is observed from this double-doped diamond thin film electroluminescence device at an applied voltage of 105 V.